The strategic and operational landscape of emergency services in the UK. Issue 1 (4th September 2019) - Murphy, Peter; Wankhade, Paresh; Lakoma, Katarzyna
Abstract : Purpose: The organisational and service delivery landscape of the emergency services in the UK has been rapidly changing and is facing further change in the foreseeable future. The purpose of this paper is to examine recent and ongoing organisational changes in the policy development, service delivery and regulatory landscape of the emergency services, in order to capture the overall picture and potential opportunities for improvement or further investigation. Design/methodology/approach: This general review utilises the characteristics of the three domains of a national framework, namely, policy development, service delivery and public assurance, and uses these characteristics as lenses to examine the three main blue light emergency services of police, fire and ambulances. Findings: What emerges in the organisational landscape and conceptual maps for the police and even more so for the Fire and Rescue Service, is the immaturity of many of the organisations in the policy and the public assurance domains while the service delivery organisations have remained relatively stable. In the relatively neglected ambulance services, we find the NHS's recent Ambulance Response Programme has considerable potential to improve parts of all three domains. Research limitations/implications: The review is limited to the UK and primarily focussed on England. Practical implications: The review identifies opportunities for improvement, potential improvement and further research. Originality/value: Although the National Audit Office has attempted in the past to provide organisational landscape reviews of individual emergency services, this contemporary comparative review of all three services using a common model is unique. It provides considerable new insights for policy makers, service delivers and regulators.